Toll-like receptor 9 antagonist suppresses humoral immunity in experimental autoimmune myasthenia gravis. (February 2018) - Zhang, Peng; Yang, Chun-lin; Liu, Ru-tao; Li, Heng; Zhang, Min; Zhang, Na; Yue, Long-tao; Wang, Cong-cong; Dou, Ying-chun; Duan, Rui-sheng
Graphical abstract: Highlights: Ablation of TLR9 signalling alleviates EAMG clinical symptoms through disrupting humoral immunity. H154 modulates antibody levels via Tfh and germinal center B cells. Suppressive ODNs of TLR9 pathway regulates B cell function by decreasing the level of TLR9 expression. Potential pharmacological strategy for myasthenia gravis. Abstract: Recent studies have demonstrated the important role of toll-like receptor 9 (TLR9) signalling in autoimmune diseases, but its role in myasthenia gravis (MG) has not been fully established. We show herein that blocking TLR9 signalling via the suppressive oligodeoxynucleotide (ODN) H154 alleviated the symptoms of experimental autoimmune myasthenia gravis (EAMG). With the downregulation of dendritic cells (DCs), TLR9 interruption reduced follicular helper T cells (Tfh) and germinal centre (GC) B cells, leading to decreased antibody production. In addition, TLR9 + B cells as well as total B cells in the spleen were inhibited by H154. These findings highlight the critical role of TLR9 in EAMG and suggest that the inhibition of the TLR9 pathway might be a potential pharmacological strategy for the treatment of myasthenia gravis.